Tumour‐derived leukaemia inhibitory factor is a major driver of cancer cachexia and morbidity in C26 tumour‐bearing mice. Issue 6 (30th September 2018) - Kandarian, Susan C.; Nosacka, Rachel L.; Delitto, Andrea E.; Judge, Andrew R.; Judge, Sarah M.; Ganey, John D.; Moreira, Jesse D.; Jackman, Robert W.
Abstract: Background: Cancer cachexia is a metabolic wasting syndrome that is strongly associated with a poor prognosis. The initiating factors causing fat and muscle loss are largely unknown. Previously, we found that leukaemia inhibitory factor (LIF) secreted by C26 colon carcinoma cells was responsible for atrophy in treated myotubes. In the present study, we tested whether C26 tumour‐derived LIF is required for cancer cachexia in mice by knockout of Lif in C26 cells. Methods: A C26 Lif null tumour cell line was made using CRISPR‐Cas9. Measurements of cachexia were compared in mice inoculated with C26 vs. C26 Lif−/− tumour cells, and atrophy was compared in myotubes treated with medium from C26 vs. C26 Lif−/− tumour cells. Levels of 25 cytokines/chemokines were compared in serum of mice bearing C26 vs. C26 Lif−/− tumours and in the medium from these tumour cell lines. Results: At study endpoint, C26 mice showed outward signs of sickness while mice with C26 Lif−/− tumours appeared healthy. Mice with C26 Lif−/− tumours showed a 55–75% amelioration of body weight loss, muscle loss, fat loss, and splenomegaly compared with mice with C26 tumours ( P < 0.05). The heart was not affected by LIF levels because the loss of cardiac mass was the same in C26 and C26 Lif−/− tumour‐bearing mice. LIF levels in mouse serum was entirely dependent on secretion from the tumour cells. Serum levels of interleukin‐6 and G‐CSF were increased by 79‐fold and 68‐fold, respectively, in C26 mice but only by five‐fold and two‐fold, respectively, in C26 Lif−/− mice, suggesting that interleukin‐6 and G‐CSF increases are dependent on tumour‐derived LIF. Conclusions: This study shows the first use of CRISPR‐Cas9 knockout of a candidate cachexia factor in tumour cells. The results provide direct evidence for LIF as a major cachexia initiating factor for the C26 tumour in vivo . Tumour‐derived LIF was also a regulator of multiple cytokines in C26 tumour cells and in C26 tumour‐bearing mice. The identification of tumour‐derived factors such as LIF that initiate the cachectic process is immediately applicable to the development of therapeutics to treat cachexia. This is a proof of principle for studies that when carried out in human cells, will make possible an understanding of the factors causing cachexia in a patient‐specific manner.